1990
DOI: 10.1111/j.1532-950x.1990.tb01156.x
|View full text |Cite
|
Sign up to set email alerts
|

Upper Airway Function during Maximal Exercise in Horses with Obstructive Upper Airway Lesions Effect of Surgical Treatment

Abstract: Upper airway pressure was measured during maximal exercise in 10 Thoroughbred racehorses with naturally occurring upper airway obstruction. Left laryngeal hemiplegia and arytenoid chondropathy resulted in substantial increases (30-40 cm H2O) in inspiratory upper airway pressure (Pl), whereas complicated aryepiglottic entrapment and subepiglottic cysts produced only modest increases (15 cm H2O) in Pl. Uncomplicated aryepiglottic entrapment and grade IV pharyngeal lymphoid hyperplasia produced only slight increa… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
38
0

Year Published

1998
1998
2020
2020

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 44 publications
(38 citation statements)
references
References 9 publications
0
38
0
Order By: Relevance
“…3,7,8 Sixteen of the 23 (70%) horses in the present study had a history of coughing. Calculation of the 95% CI suggested that between 47% and 85% of mature nonracehorses with epiglottic abnormalities will be examined because of coughing, emphasizing the importance of a comprehensive diagnostic evaluation, including upper airway endoscopy, in horses examined because of coughing.…”
Section: Discussionmentioning
confidence: 97%
See 1 more Smart Citation
“…3,7,8 Sixteen of the 23 (70%) horses in the present study had a history of coughing. Calculation of the 95% CI suggested that between 47% and 85% of mature nonracehorses with epiglottic abnormalities will be examined because of coughing, emphasizing the importance of a comprehensive diagnostic evaluation, including upper airway endoscopy, in horses examined because of coughing.…”
Section: Discussionmentioning
confidence: 97%
“…1 Epiglottic abnormalities can cause partial obstruction of the rima glottis, causing respiratory noise and exercise intolerance in Thoroughbred and Standardbred racehorses. 2,3 Epiglottic entrapment can also precede development of DDSP in racehorses. 4 The most common complaints in racehorses with epiglottic abnormalities are respiratory noise and exercise intolerance, rather than coughing and nasal discharge.…”
mentioning
confidence: 98%
“…During exercise large pressure changes occur in the upper respiratory tract (Derksen et al, 1986). Studies of upper airway flow mechanics in exercising horses have made it clear that identification of an upper airway function abnormality does not necessarily mean a functional airurray obstruction when the horse is exercising (Stick and Derksen,1989;Williams et al, 1990). On the other hand, the abscence of an upper airway abnormality at rest does not rule out a functional obstruction during strenous exercise (Morris and Seeherman,7990).…”
Section: Resultsmentioning
confidence: 99%
“…The horse is able to swallow during strenuous exercise; the reflex is intact with full adduction of the arytenoid cartilages, which then return to the fully abducted position. Horses may swallow several times during exercise, but repeated swallowing indicates an irritation or hypersecretion as in COPD affected horses (Morriq 1991) Abnormal Function of the Upper Ainuays Obstructing functional abnormalities observed during exercise are intermittent DDSP 1990;Stick et al, 1991;Parente et at., 1994;Hackett et al, 1994;Parente and Martin, 1995;Lumsden et al, 1995;Kannegieter and Dore, 1995)[Figs 2a-b], LH or dynamic arytenoid cartilage collapse (Morris and Seeherman, 7990;Stick et al, 1991;Morris and Seeherman, 1991;Rakestraw et al, 1991;Parente et al, 1994, Parente andMartin, 1995;Kannegieter and Dore, 1995;Lumsden et al, 1.995) [Figs.2c-d], intermittent EE Seeherman, 1991, Hackett et al, 1994;Kannegieter and Dore, 1995;Lumsden et al, 1995;Weishaupt et al, 1997), permanent EE with obstructing aryepiglottio folds (Morris and Seeherman,1.990), aryepiglottic fold collapse (Hackett et al, 1994;Kannegieter and Dore, 1995;Parente and Martin, 1995), aryepiglottic fold flutter (Kannegieter and Dore, 7995)vocalfold prolapse (Hackett et al, 1994;Lumsden et al, 1995), vocal cord flutter (Kannegieter and Dore, 1995), epiglottic retroversion (Parente and Marlin, 1995;Derksen et al, 1997), epiglottic flutter (Kannegieter and Dore,7995), collapse of the roof of the nasopharynx (Strand and Staempfli, 1993;…”
Section: Observ Atio Ns D U Ri N G Exerc I Sementioning
confidence: 99%
“…If air flow measurements are not available, trans-upper airway pressure during exercise can yield useful information (Williams et al 1990). As horses begin to exercise, air flows increase in response to increased trans-upper airway pressures.…”
Section: Figmentioning
confidence: 99%